“Arrival In Words” – Reflections on Language in German Migration Literature: (in German language) - Patsovska-Ivanova, Eva (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The article is based on the works of three German-speaking authors with a migration background: Abbas Khider, Saša Stanišić and Marica Bodrožić. Against the background of a linguistic and stylistic analysis of passages from selected texts, the authors’ different approaches to the German language, which was originally foreign to them, are reflected on. Whether the ironic attitude of Abbas Khider in Deutsch für alle. Das endgültige Lehrbuch (2019), the loving, confidentially-conspiratorial use of language by Marica Bodrožić in Sterne erben, Sterne färben (2007) or the multi-layered approach of Saša Stanišić in Herkunft (2019), which combines semantic characteristics with narrative methods – all these procedures reflect a certain way of coping with reality. A necessary act of coping with reality that results from the life-changing experiences they have had as well as from the need for language integration and self-determination. As a further step, the identified approaches to language are related to the revised identity concepts and justified theoretically. Linguistic studies on migration literature such as those by Uwe Hinrichs serve as a theoretical basis as well as cultural theoretical approaches such as those by Homi K. Bhabha and other researchers on inter- and transculturality. Particular attention is paid to the reflections on language and its role in the search for one’s own identity that the authors themselves have integrated into the selected works.
Keywords: language; migration literature; Saša Stanišić; Abbas Khider; Marica Bodrožić